Strategi Kreatif Program Web Series Keluarga Badak Episode 1 Di Kanal Youtube Space# - Cakra Mahardhika Kevlana; Syaifuddin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
A program can be said to be succesfull if it can make the audience enjoy the show. Included also in form of web series program. To achieve that goal, creative strategies are one way to make a program more interesting. The purpose of this research is to find out the creative strategi of episode 1 Keluarga Badak web series program on YouTube Space# channel. With this research, we can find out what creative srategies the episode 1 Keluarga Badak team used. The method in this study used a descriptive qualitative approach with interview and literacy technique to obtain more accurate results. This study uses the post – positivism paradigm and uses the Herbert Zettl program strategi as a reference to analyze the data obtained. The results obtained are the season 1 episode 1 Keluarga Badak can convey the message that has been formed by the creative team to the audience, with a strategy that refers to the selection of names, selection of players, and the concept of program.